2021
DOI: 10.1039/d0cs00918k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical methods for the transfer of electrons and exchange of ions: inorganic reactivity from nanoparticles to organometallics

Abstract: For inorganic metathesis and reduction reactivity, mechanochemistry is demonstrating great promise towards both nanoparticles and organometallics syntheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 214 publications
0
27
0
Order By: Relevance
“…In recent years, the growing interest in this class of reactions got an important role in promoting the development of suitable synthetic protocols to ensure efficient redox protocols [150] and minimize the environmental impact of these synthetic strategies [146] . In this context, we observed a resurgence of proof concepts developed about a century ago by Ciamician and based on sunlight or some of its components as the green energy source [151] .…”
Section: Mechanochemistry Vs Solvent‐based Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the growing interest in this class of reactions got an important role in promoting the development of suitable synthetic protocols to ensure efficient redox protocols [150] and minimize the environmental impact of these synthetic strategies [146] . In this context, we observed a resurgence of proof concepts developed about a century ago by Ciamician and based on sunlight or some of its components as the green energy source [151] .…”
Section: Mechanochemistry Vs Solvent‐based Chemistrymentioning
confidence: 99%
“…In organic chemistry, redox processes are one of three types of reactions (addition reactions, substitution reactions, and elimination reactions) that govern most reactions and are still one of the most widely studied topics in chemistry today. [149] In recent years, the growing interest in this class of reactions got an important role in promoting the development of suitable synthetic protocols to ensure efficient redox protocols [150] and minimize the environmental impact of these synthetic strategies. [146] In this context, we observed a resurgence of proof concepts developed about a century ago by Ciamician and based on sunlight or some of its components as the green energy source.…”
Section: Mechanochemistry In Redox Processes Promoted By Piezoelectri...mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15] The advantage of these milling processes is the simplicity of the single-step production of TMCs, primarily because of its capabilities of alloying materials with way different melting points. A recent review of the synthesis of TMCs showed that the binary suldes [4][5][6] are most explored with this technique due to their applications as catalytic materials, 16 in lithium-ion batteries, 17,18 and in solution-processed solar cells, 19 where the binary selenides and tellurides still are to be better exploited.…”
Section: Introductionmentioning
confidence: 99%
“…when the reduction of cinnabar to mercury was reported. 3 Modern understanding of its alloying procedure of synthesis is viewed on the bases of the transfer of electrons and ion exchanges in a highly entropic environment created by the milling, 4 which can promote the formation of unique metastable phases. The most employed types of equipment in this field are the high-energy ball mills, where the vibratory or planetary setups are of most common use.…”
Section: Introductionmentioning
confidence: 99%
“…Continuously increasing environmental awareness in the recent decades has encouraged the development of many sustainability-driven initiatives, defined within the Twelve Principles of Green Chemistry, aiming at enhanced efficiency and environmental safety of chemical processes. , In this notion, the mechanically induced solid state chemical transformations have been elevated from mere curiosity to a dynamically growing research field providing highly efficient alternatives to the classic solution-based synthetic methods , Within this recent advent of mechanochemistry, a broad range of remarkable developments have been demonstrated in synthetic organic and inorganic chemistry, as well as materials science. One of the emerging research fields in this area concerns mechanically induced chemical reactions at the gas–solid interface . With regard to the principles of green chemistry development of gas–solid-state small-molecule ball-milling processes involving CO 2 would be highly desirable, but this research field is still at its infancy with only a handful of reports in the past decade.…”
Section: Introductionmentioning
confidence: 99%